The Role of Telehealth in Enhancing Chronic Disease Management in Rural Areas - Adnan Ramadan Al Khanfar; Ameera Jawad Al shulian; Amal Abdullah Alomran; Zahra Abbas Alshehab; Fatimah Abdulrazaq Alhumood; Murtadah Yassin Hirabah; Ahmed Mohammed Alabbad; Ghufran Sadeq Al Sanni; Fatimah Abbas Alnajjar; Ahmed Hussain Alkuwaythim; Ali Hussain Alkuwaythim; Wasayf Ibrahim Almulhim; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Telehealth has become a pivotal tool in modern healthcare, especially for managing chronic diseases in remote area where approach to medical services is oftenrestricted.Chronic diseases such as diabetes and hypertension disproportionately affect rural populations due to limited healthcare access, geographic isolation, and socioeconomic barriers.This research seeks to determine the impact that telehealth has on chronic diseases such as diabetics. The existing conservative management approaches within these areas involves personal contacted based consultations which are tiresome, costly and slows down early diagnosis and more so early treatments. Often, these approaches result in less than desirable patient health, late treatment, and higher costs for the patients. In order to respond to these challenges, this study outlines the novel telehealth model specific to the rural context. Therefore, the novelty of this study is the utilization of top-notch telehealth technologies, such as the IoT, AI, for developing a sustainable healthcare system. The research plans include quantitative questionnaires and Chi-Square analyses to assess demographic barriers to the use of telehealth, coupled with the shared telehealth interventions that include video consultations and IoT-Health Monitoring.The result show positive trends in health status: patients’ HbA1c lowering from 8.5% to 7.2%, blood pressure from 140/90 to 125/80, and patient compliance increased from 65% to 85%. Moreover, telehealth evidenced the effectiveness of its application in increasing the number of consultations and decreasing the travelling expenses by patients, above 90-percent overall. This research not only highlights the transformative potential of telehealth in managing chronic diseases but also identifies barriers such as technology access disparities and privacy concerns.